Solid-State Synthesis and Effect of Temperature on Optical Properties of CuO Nanoparticles - Vidyasagar, C. C.; Naik, Y. Arthoba; Venkatesha, T. G.; Viswanatha, R. (Nano-Micro Letters, 2012)
Modulation of band energies through size control offers new ways to control photoresponse and photoconversion efficiency of the solar cell. The P-type semiconductor of copper oxide is an important functional material used for photovoltaic cells. CuO is attractive as a selective solar absorber since it has high solar absorbance and a low thermal emittance. The present work describes the synthesis and characterization of semiconducting CuO nanoparticles via one-step, solid-state reaction in the presence of Polyethylene glycol 400 as size controlling agent for the preparation of CuO nanoparticles at different temperatures. Solid-state mechanochemical processing, which is not only a physical size reduction process in conventional milling but also a chemical reaction, is mechanically activated at the nanoscale during grinding. The present method is a simple and efficient method of preparing nanoparticles with high yield at low cost. The structural and chemical composition of the nanoparticles were analyzed by X-ray diffraction, field emission scanning electron microscopy and energy-dispersive spectrometer, respectively. Optical properties and band gap of CuO nanoparticles were studied by UV-Vis spectroscopy. These results showed that the band gap energy decreased with increase of annealing temperature, which can be attributed to the improvement in grain size of the samples.